2016
DOI: 10.1007/s10461-016-1610-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Depression and Condom Use Differs by Sexual Behavior Group in Patients with HIV

Abstract: Identifying a relationship between depression and sexual risk behavior in HIV-infected patients could establish a mechanism to enhance prevention efforts. We conducted a cross-sectional analysis using data from the University of Pennsylvania Center for AIDS Research and used ordinal logistic regression to measure the association between depression and non-condom use. 716 men who have sex with men (MSM), 262 heterosexual men and 277 heterosexual women were included. The association between depression and non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Studies have shown that the prevalence rates of anxiety among MSM in Zhejiang and Chongqing, China, were 24.0% and 31.97%, respectively. Besides, previous studies have reported that poor mental health such as anxiety and depression are related to the HIV risk of MSM ( Babowitch et al, 2018 ; Brickman et al, 2017 ; Chen & Raymond, 2017 ; Fendrich et al, 2013 ; Lelutiu-Weinberger et al, 2013 ; Pan et al, 2017 ; Watkins et al, 2016 ). For instance, the higher the level of depressive symptoms reported by MSM, the more likely they are to have unprotected anal sex ( Fendrich et al, 2013 ); anxiety has also been identified as an independent predictor of sexual risk ( Lelutiu-Weinberger et al, 2013 ).…”
mentioning
confidence: 98%
“…Studies have shown that the prevalence rates of anxiety among MSM in Zhejiang and Chongqing, China, were 24.0% and 31.97%, respectively. Besides, previous studies have reported that poor mental health such as anxiety and depression are related to the HIV risk of MSM ( Babowitch et al, 2018 ; Brickman et al, 2017 ; Chen & Raymond, 2017 ; Fendrich et al, 2013 ; Lelutiu-Weinberger et al, 2013 ; Pan et al, 2017 ; Watkins et al, 2016 ). For instance, the higher the level of depressive symptoms reported by MSM, the more likely they are to have unprotected anal sex ( Fendrich et al, 2013 ); anxiety has also been identified as an independent predictor of sexual risk ( Lelutiu-Weinberger et al, 2013 ).…”
mentioning
confidence: 98%
“…24 An American study confirmed a relationship between depression and the failure to use condoms in PLWH with uninfected partners. 26 In our study, depression was more common in men than in women. Shadloo et al evaluated the prevalence of psychological issues amongst Iranian PLWH: mood disorders, including major depressive disorder, were more prevalent in males than females (34.5% vs. 28.8%, respectively).…”
Section: Discussionmentioning
confidence: 42%
“… 24 An American study confirmed a relationship between depression and the failure to use condoms in PLWH with uninfected partners. 26 …”
Section: Discussionmentioning
confidence: 99%
“…We choose six estimator values of 50, 100, 200, 300, 400, and 500, five minimum child weight values of 1, 2, 3, 4, and 5, and five regularization alpha values of 1e-5, 1e-3, 1e-2, 0.1, and 1. The search ranges for learning rate, maximum tree depth, subsample and colsample_bytree were [0.05,0.2], ( 3 , 11 ), [0.5,1] and [0.5,1], respectively. We carefully tuned the parameters of the XGBoost algorithm to obtain the best performance, the final XGBoost model parameter settings are described in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Suffering from disproportionate rates of stigma and discrimination ( 3 , 4 ), MSM experience remarkably poorer mental health ( 5 ). And evidence has demonstrated that HIV risk ( 6 – 9 ), amphetamine-type-stimulants (ATS) use and homosexuality-related stigma ( 10 ), and sexual risk behaviors ( 11 , 12 ) are associated with depression among MSM population. Therefore, it is of crucial importance to develop reliable and efficient methods for detection and early warning of the depressive emotions or mental health among MSM population, and enable those suffering from depression to be more proactive about their mental health.…”
Section: Introductionmentioning
confidence: 99%